GhWRKY41 forms a positive feedback regulation loop and increases cotton defence response against Verticillium dahliae by regulating phenylpropanoid metabolism. Issue 5 (3rd February 2023) - Xiao, Shenghua; Ming, Yuqing; Hu, Qin; Ye, Zhengxiu; Si, Huan; Liu, Shiming; Zhang, Xiaojun; Wang, Weiran; Yu, Yu; Kong, Jie; Klosterman, Steven J.; Lindsey, Keith; et al.
Summary: Despite the established significance of WRKY proteins and phenylpropanoid metabolism in plant immunity, how WRKY proteins modulate aspects of the phenylpropanoid pathway remains undetermined. To understand better the role of WRKY proteins in plant defence, we identified a cotton ( Gossypium hirsutum ) protein, GhWRKY41, that is, universally and rapidly induced in three disease‐resistant cotton cultivars following inoculation with the plant pathogenic fungus, Verticillium dahliae . We show that overexpression of GhWRKY41 in transgenic cotton and Arabidopsis enhances resistance to V. dahliae, while knock‐down increases cotton more susceptibility to the fungus. GhWRKY41 physically interacts with itself and directly activates its own transcription. A genome‐wide chromatin immunoprecipitation and high‐throughput sequencing (ChIP‐seq), in combination with RNA sequencing (RNA‐seq) analyses, revealed that 43.1% of GhWRKY41‐binding genes were up‐regulated in cotton upon inoculation with V. dahliae, including several phenylpropanoid metabolism master switches, receptor kinases, and disease resistance‐related proteins. We also show that GhWRKY41 homodimer directly activates the expression of GhC4H and Gh4CL, thereby modulating the accumulation of lignin and flavonoids. This finding expands our understanding of WRKY‐WRKY protein interactions and provides important insights into the regulation of the phenylpropanoid pathway in plant immune responses by a WRKY protein.